Altered neuronal habituation to hearing others’ pain in adults with autistic traits - Meng, Jing (Sci Rep, 2020)
This study tested the hypothesis that autistic traits influence the neuronal habituation that underlies the processing of others’ pain. Based on their autism-spectrum quotient (AQ), two groups of participants were classified according to their autistic traits: High-AQ and Low-AQ groups. Their event-related potentials in response to trains of three identical audio recordings, exhibiting either painful or neutral feelings of others, were compared during three experimental tasks. (1) In a Pain Judgment Task, participants were instructed to focus on pain-related cues in the presented audio recordings. (2) In a Gender Judgment Task, participants were instructed to focus on non-pain-related cues in the presented audio recordings. (3) In a Passive Listening Task, participants were instructed to passively listen. In the High-AQ group, an altered empathic pattern of habituation, indexed by frontal-central P2 responses of the second repeated painful audio recordings, was found during the Passive Listening Task. Nevertheless, both High-AQ and Low-AQ groups exhibited similar patterns of habituation to hearing others’ voices, both neutral and painful, in the Pain Judgment and Gender Judgment Tasks. These results suggest altered empathic neuronal habituation in the passive processing of others’ vocal pain by individuals with autistic traits.